A function is defined as above. Evaluate: .
Details and Assumptions :
denotes the greatest integer less than or equal to .
It is and not .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The problem is actually based on a single conjecture which is
⌊ 2 x ⌋ + ⌊ 2 x + 1 ⌋ = ⌊ x ⌋ ∀ x ∈ R Firstly, I will prove the conjecture.
Let ⌊ x ⌋ = I and { x } = f , where I is an integer and f is a fraction ( 0 ≤ f < 1 ) .
Case 1 : I is even, i.e., I = 2 p for some integer p .
⇒ ⌊ 2 x ⌋ = ⌊ 2 I + f ⌋ = ⌊ 2 2 p + f ⌋ = ⌊ p + 2 f ⌋ = p
⇒ ⌊ 2 x + 1 ⌋ = ⌊ 2 I + f + 1 ⌋ = ⌊ 2 2 p + f + 1 ⌋ = ⌊ p + 2 f + 1 ⌋ = p
⇒ ⌊ 2 x ⌋ + ⌊ 2 x + 1 ⌋ = p + p = 2 p = I = ⌊ x ⌋
Case 2 : I is odd, i.e., I = 2 p + 1 for some integer p .
⇒ ⌊ 2 x ⌋ = ⌊ 2 I + f ⌋ = ⌊ 2 2 p + 1 + f ⌋ = ⌊ p + 2 f + 1 ⌋ = p
⇒ ⌊ 2 x + 1 ⌋ = ⌊ 2 I + f + 1 ⌋ = ⌊ 2 2 p + f + 2 ⌋ = ⌊ p + 1 + 2 f ⌋ = p + 1
⇒ ⌊ 2 x ⌋ + ⌊ 2 x + 1 ⌋ = p + p + 1 = 2 p + 1 = I = ⌊ x ⌋ .
Hence, Proved. Now we would apply this repeatedly by replacing with different values.
x → z x → 2 z x → 4 z ⋮ ⇒ ⌊ 2 z ⌋ + ⌊ 2 z + 1 ⌋ = ⇒ ⌊ 4 z ⌋ + ⌊ 4 z + 2 ⌋ = ⇒ ⌊ 8 z ⌋ + ⌊ 8 z + 4 ⌋ = ⋮ ⌊ z ⌋ ⌊ 2 z ⌋ ⌊ 4 z ⌋ ⋮
Adding all of these, we obtain, ⌊ 2 z + 1 ⌋ + ⌊ 4 z + 2 ⌋ + ⌊ 8 z + 4 ⌋ + ⋯ + = ⌊ z ⌋ ⇒ r = 1 ∑ ∞ ⌊ 2 r z + 2 r − 1 ⌋ = ⌊ z ⌋
Therefore, f ( x ) = ⌊ x ⌋ ⇒ f ( 2 0 . 1 4 ) = 2 0